2017
DOI: 10.1039/c7lc00694b
|View full text |Cite
|
Sign up to set email alerts
|

Stereolithographic printing of ionically-crosslinked alginate hydrogels for degradable biomaterials and microfluidics

Abstract: 3D printed biomaterials with spatial and temporal functionality could enable interfacial manipulation of fluid flows and motile cells. However, such dynamic biomaterials are challenging to implement since they must be responsive to multiple, biocompatible stimuli. Here, we show stereolithographic printing of hydrogels using noncovalent (ionic) crosslinking, which enables reversible patterning with controlled degradation. We demonstrate this approach using sodium alginate, photoacid generators and various combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 95 publications
(113 reference statements)
0
43
0
Order By: Relevance
“… 247 , 255 Additionally, besides using photo-cross-linking, noncovalently cross-linked alginate hydrogels have also been processed with DLP, via the incorporation of photoacid moieties in the ink formulation, to tune the rate of ionic bonds formation between calcium cations and the anionic alginate chains. 266 …”
Section: Implications For Lithography-based Printing Technologiesmentioning
confidence: 99%
“… 247 , 255 Additionally, besides using photo-cross-linking, noncovalently cross-linked alginate hydrogels have also been processed with DLP, via the incorporation of photoacid moieties in the ink formulation, to tune the rate of ionic bonds formation between calcium cations and the anionic alginate chains. 266 …”
Section: Implications For Lithography-based Printing Technologiesmentioning
confidence: 99%
“…The authors observed that monolayers with an initially convex geometry were pulled forward faster than flat geometries due to supramolecular actomyosin cables ( Figure a). [ 279 ]…”
Section: Topographical Patterning Of Hydrogel Substratesmentioning
confidence: 99%
“…The next step in the fabrication of a biomimetic in vitro neurovascular model involves integrating the latest advances in iPSC derivation methods along with tissue engineering approaches for generating capillary-sized vascular structures. As opposed to extrusion-based 3D printing, projection stereolithographic printing techniques can produce 3D scaffolds with complex integrated fluidic channels (diameters as small as 20 μm) through spatially controlled cross-linkage of photosensitive prepolymer solution by targeted light exposure, delivered by computer-controlled digital micro-mirror assemblies or through a 2D “mask” in a layer-by layer fashion (Hribar et al, 2015 ; Wang et al, 2015 ; Raman et al, 2016 ; Valentin et al, 2017 ). Laser-assisted printing operates in a similar fashion, except that the laser focus is traditionally “patterned” by CAD file and, in the case of two-photon systems utilizing pulsed femtosecond laser sources, has achieved pattering of hydrogel features as small as 10 μm (Hoffmann and West, 2013 ).…”
Section: Routes For Engineering Complex In Vitro Nmentioning
confidence: 99%